Cyberbullying victimization and somatic complaints: A prospective examination of cognitive emotion regulation strategies as mediators. - Rey-Peña, Lourdes; Neto, Félix; Extremera-Pacheco, Natalio (Elsevier, 2020)
Background/Objective: The main purpose of this study was to examine the relationships among cybervictimization, maladaptive cognitive emotion regulation strategies and somatic complaints in a 4-month follow-up study. Method: A total of 1,024 high school students (456 male and 568 female, M (SD) = 13.69 years (1.3 years), range 12---18 years, voluntarily participated in this study. Measures of cybervictimization and cognitive strategies were obtained at Time 1. Four months later (Time 2), measures of somatic complaints were obtained. Results: Multiple mediation analyses were conducted to determine the mediating roles of maladaptive strategies in the link between cybervictimization and somatic complaints. As expected, pathanalytic results showed that cybervictimization predicted somatic symptoms. Furthermore, some maladaptive regulation strategies, namely self-blame and rumination, partially mediated the link between cybervictimization and somatic symptoms evaluated 4-months later. Conclusions: The findings are discussed in terms of the role that maladaptive cognitive emotion regulation strategies might play with regards to physical health in cyberbullying episodes. In general, these findings have important implications for developing an understanding about the affective determinants of somatic health problem initiation and maintenance after a victimization and for developing intervention programs specifically for cybervictimized adolescents.
Cibervictimización y quejas somáticas: examen prospectivo de las estrategias de regulación cognitivo-emocional como mediadores.
Keywords: Ciberacoso; Internet y jóvenes; Cyberbullying; Cognitive emotion; Somatic complaints; Physical health; Ex post facto study; Regulation strategies